Geochronology and geochemistry of the Sangri Group Volcanic Rocks, Southern Lhasa Terrane: Implications for the early subduction history of the Neo-Tethys and Gangdese Magmatic Arc - Kang, Z.; Xu, J.; Wilde, Simon; Feng, Z.; Chen, J.; Wang, B.; Fu, W.; Pan, H. (Elsevier BV, 2014)
The Sangri Group volcanic rocks are distributed along the southern margin of the Lhasa Terrane on the northern side of the Indus-Yarlung Zangbo suture zone. This Group consists of the Mamuxia and Bima formations and has long been considered to be Late Jurassic to Early Cretaceous in age. In this paper, we report for the first time zircon LA-ICPMS U-Pb ages, whole-rock major and trace element geochemistry, as well as Sr-Nd isotope data of the Bima Formation volcanic rocks in the Sangri County, Tibet. Two samples collected from the Bima Formation volcanic rocks yield zircon U-Pb ages of 195 ± 3 Ma and 189 ± 3 Ma, respectively. These data suggest that the Bima Formation volcanic rocks formed during the Early Jurassic rather than the Late Jurassic-Early Cretaceous as previously reported. The volcanic rocks of the Bima Formation are dominantly composed of basalt and andesite that are enriched in LILEs and LREEs, but depleted in HFSEs, showing typical characteristics of arc volcanic rocks. They also show positive εNd (t) (+ 4.09 to + 7.02) values and low initial 87Sr/86Sr (0.7032 to 0.7050) ratios, similar to the MORB of the Indus-Yarlung Zangbo ophiolites, indicating that the Bima Formation volcanic rocks were derived from a depleted mantle wedge. The magmas subsequently experienced juvenile crust contamination and fractional crystallization during ascent. Geochemical features of magmas of the Bima Formation volcanic rocks are interpreted to be generated by the northward subduction of Neo-Tethys beneath the southern Lhasa Terrane as early as ~ 195 Ma. Coeval with a large volume of Late Triassic-Early Jurassic felsic intrusions within the Gangdese arc, the Gangdese magmatic arc is interpreted to be initiated at a juvenile continental margin during the Late Triassic-Early Jurassic, although a possible intra-oceanic arc setting cannot be excluded.